(Re)Thinking think tanks in the age of policy labs: The rise of knowledge‐based policy influence organisations. Issue 1 (22nd December 2021) - Wellstead, Adam M.; Howlett, Michael
Abstract: The idea of 'think tanks' is one of the oldest in the policy sciences. Although the topic has been studied for decades, recent works dealing with advocacy groups, policy and behavioural insight labs and into the activities of think tanks themselves have led to discontent with the definitions used in the field, and especially with the way the term may obfuscate rather than clarify important distinctions between the different kinds of knowledge‐based policy influence organisations (KBPIO) operating in the contemporary policy landscape. In this paper, we examine the traditional and current definitions of think tanks utilised in the discipline and point out their weaknesses. We then develop a new framework to better capture the variation in the kinds of knowledge‐based organisations which operate in many sectors. Abstract : We examine and critique popular academic definitions of think tanks. An additional challenge has been the rise of new kinds of knowledge‐based policy influence organizations (KBPIO) across the policy advice landscape (e.g., research institutes, policy labs, and behavioural insight teams). A diagnostic framework is introduced that captures these distinctions.